Perceptions of Corruption in Higher Education among Alumni of the Leading Russian Universities - O. S. Deyneka; L. N. Dukhanina; D. V. Krylova; A. A. Maksimenko (Высшее образование в России)
The article analyzes current trends in the study of corruption in the higher education system in Russia and Western countries. Classifications of corruption abuse, the structure of corruption indicators in universities, problems of studying attitudes towards corruption in the higher education system and the reflection of abuse in the media are discussed. The results of a survey of graduates of seven leading Russian universities for the period from September 2019 to January 30, 2020 are presented. Using the authors’ questionnaire, 1,468 graduates of 2013 and 2018 were interviewed. An additional task was also performed to compare anti-corruption materials on the websites of seven leading Russian universities. The results of the survey indicate the positive dynamics of students’ perceptions of corruption offenses in the direction of decreasing their frequency, which, along with site analysis data, indicates a systematic work that has been carried out in each of the universities over the past years. The authors note the need for greater awareness among university students and teachers about the various situations of corruption, as well as the creation of a feedback about the possible cases of abuse in the university environment that is safe for an applicant.